Electrocardiographic Markers Indicating Right Ventricular Outflow Tract Conduction Delay as a Predictor of Major Arrhythmic Events in Patients With Brugada Syndrome: A Systematic Review and Meta-Analysis - Iqbal, Mohammad; Putra, Iwan Cahyo Santosa; Pranata, Raymond; Budiarso, Michael Nathaniel; Pramudyo, Miftah; Goenawan, Hanna; Akbar, Mohammad Rizki; Kartasasmita, Arief Sjamsulaksan (Frontiers in Cardiovascular Medicine, 2022)
Introduction Risk stratification in Brugada Syndrome (BrS) patients is still challenging due to the heterogeneity of clinical presentation; thus, some additional risk markers are needed. Several studies investigating the association between RVOT conduction delay sign on electrocardiography (ECG) and major arrhythmic events (MAE) in BrS patients showed inconclusive results. This meta-analysis aims to evaluate the association between RVOT conduction delay signs presented by aVR sign and large S wave in lead I, and MAE in BrS patients. Methods The literature search was performed using several online databases from the inception to March 16th, 2022. We included studies consisting of two main components, including ECG markers of RVOT conduction delay (aVR sign and large S wave in lead I) and MAE related to BrS (syncope/VT/VF/SCD/aborted SCD/appropriate ICD shocks) Results Meta-analysis of eleven cohort studies with a total of 2575 participants showed RVOT conduction delay sign was significantly associated with MAE in BrS patients (RR=1.87(1.35,2.58);p<0.001;I2=52%,Pheterogeneity=0.02). Subgroup analysis showed that aVR sign (RR=2.00(1.42,2.83);p<0.001;I2=0%,Pheterogeneity=0.40) and large S wave in lead I (RR=1.74(1.11,2.71);p=0.01;I2=60%,Pheterogeneity=0.01) were significantly associated with MAE. Summary receiver operating characteristics analysis revealed the aVR sign [AUC:0.77(0.73-0.80)] and large S wave in lead I [AUC:0.69(0.65-0.73)] were a good predictor of MAE in BrS patients. Conclusion RVOT conduction delay sign, presented by aVR sign and large S wave in the lead I, is significantly associated with an increased risk of MAE in BrS patients. Hence, we propose that these parameters may be useful as an additional risk stratification tool to predict MAE in BrS patients.